The Effect of Crude Oil Prices on Economic Growth in South East Sulawesi, Indonesia: An Application of Autoregressive Distributed Lag Model - Saidi, La Ode; Adam, Pasrun; Rahim, Manat; Rosnawintang, Rosnawintang (International Journal of Energy Economics and Policy, 2019)
This research aims to examine the effect of crude oil prices on economic growth in South East Sulawesi, Indonesia. Data on crude oil prices and economic growth are annual time series data stretching from 1987 to 2016. The results of co-integration tests show that there is no long-term relationship between crude oil prices and economic growth. However, the estimation of the ARDL(5.0) model shows that in the short term, there is the influence of crude oil prices toward economic growth. Keywords: Crude oil price, economic growth, ARDL bound co-integration test, ARDL model JEL Classifications: C120, C320, E300, O470 DOI: https://doi.org/10.32479/ijeep.7322